Socialist joy in the writing of Langston Hughes - Scott, Jonathan, 1968- (University of Missouri Press, 2006)
"Explores Hughes's intellectual method and its relation to social activism. Examines his involvement with socialist movements of the 1920s and 1930s and contends that the goal of overthrowing white oppression produced a "socialist joy" expressed repeatedly in his later work, in spite of the anticommunist crusades of the cold war"--Provided by publisher.